2007
DOI: 10.1007/s00404-007-0421-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of triple-marker test results with adverse pregnancy outcomes in low-risk pregnancies with healthy newborns

Abstract: Serum estriol, AFP or HCG values in triple test results may be associated with development of oligohydramnios, gestational diabetes and macrosomia in women with healthy and normal appearing fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
0
22
3
Order By: Relevance
“…17:20 Discrepancies between our findings and others include our null finding with respect to early preterm birth and increased nuchal translucency 17;22;33 and also the numerous reports of an association between preterm birth and second trimester abnormalities in hCG and uE3 – including patterns reported by some from our group. 21;26;34 While we suspect that the differences between our study and others with respect to NT may be due to our having too few pregnancies with increased NT in our study to be able to explore this relationship in detail, the difference between our study and other studies with respect to second trimester hCG and uE3 may be a result of our ability to consider both first and second trimester markers together.…”
Section: Commentcontrasting
confidence: 59%
“…17:20 Discrepancies between our findings and others include our null finding with respect to early preterm birth and increased nuchal translucency 17;22;33 and also the numerous reports of an association between preterm birth and second trimester abnormalities in hCG and uE3 – including patterns reported by some from our group. 21;26;34 While we suspect that the differences between our study and others with respect to NT may be due to our having too few pregnancies with increased NT in our study to be able to explore this relationship in detail, the difference between our study and other studies with respect to second trimester hCG and uE3 may be a result of our ability to consider both first and second trimester markers together.…”
Section: Commentcontrasting
confidence: 59%
“…It was concluded that the triple test can be used not only for the detection of fetal chromosomal and neural tube defect abnormalities but also for the detection of high-risk pregnancies (16). Recently published data has shown that serum unconjugated estriol, AFP or hCG values in triple test results may be associated with development of oligohydramnios, gestational diabetes and macrosomia in women with healthy and normal appearing fetuses (17). Despite the increase in prematurity and low birth weight, unexplained raised levels of AFP were not associated with an increase in perinatal mortality (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that maternal serum markers in the second trimester can predict adverse birth outcomes. 20,21 Whether the concentration of maternal AFP and β-HCG can predict inverse birth outcomes is inconsistent. Previous research reported that maternal AFP above 2 MoM increased the risk of PTB.…”
Section: Discussionmentioning
confidence: 99%